2018
DOI: 10.6060/tcct.20165909.17y
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Nitrogen-Doped Amorphous Carbon Coatings Obtained by Impulse Vacuum-Arc Method

Abstract: The paper presents results of the research of the structure and properties of nitrogen-doped amorphous carbon coatings obtained in the vacuum from the flow of pulsed carbon plasma. The doping by nitrogen of carbon coating was determined to lead to increases in electrical conductivity, reductions of internal stresses, reduce of density, hardness and modulus, and to the change in structure, surface morphology and tribological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The pulse vacuum arc technique for obtaining diamond-like carbon coatings [3] has a number of advantages over other methods. The authors of [4] reported the results of complex studies concerning the structure and properties of nitrogen-doped amorphous carbon coatings (a-C:N) obtained in vacuum using a pulsed carbon plasma flow. It was established that the nitrogen doping of a carbon coating leads to an increase in electrical conductivity, to a decrease in internal stresses, to a decrease in density, hardness, and elastic modulus, and to a change in the structure, surface morphology, and tribological characteristics as compared to an undoped coating (ta-C).…”
Section: Introductionmentioning
confidence: 99%
“…The pulse vacuum arc technique for obtaining diamond-like carbon coatings [3] has a number of advantages over other methods. The authors of [4] reported the results of complex studies concerning the structure and properties of nitrogen-doped amorphous carbon coatings (a-C:N) obtained in vacuum using a pulsed carbon plasma flow. It was established that the nitrogen doping of a carbon coating leads to an increase in electrical conductivity, to a decrease in internal stresses, to a decrease in density, hardness, and elastic modulus, and to a change in the structure, surface morphology, and tribological characteristics as compared to an undoped coating (ta-C).…”
Section: Introductionmentioning
confidence: 99%